The Effect of Social Media Use and Environment on Mental Health Among Young People in Sukabumi - Yana Priyana (West Science Interdisciplinary Studies, 2023)
This study looked into how social media use and outside influences affected young people's mental health in Sukabumi, Indonesia. 400 young individuals between the ages of 18 and 25 participated in a cross-sectional survey in which information on social media use, environmental exposure, and mental health outcomes (such as depression, anxiety, and stress) was gathered. According to the findings, increased social media use was linked to greater levels of stress, anxiety, and depression, but exposure to environmental elements including noise, air pollution, and green open spaces was found to be a significant predictor of mental health outcomes. In particular, increased exposure to green space was linked to lower levels of sadness, anxiety, and stress whereas higher exposure to air and noise pollution was linked to higher levels of these emotions. Gender was also found to be a significant predictor, with women reporting higher levels of depression, anxiety, and stress than men. These findings highlight the importance of considering the role of social media use, environmental factors, and gender in understanding mental health outcomes among young people in Sukabumi. Interventions aimed at promoting mental health among young people should consider social media use, environmental factors, and gender-related factors. Limitations of the study include a cross-sectional design and limited generalizations to other populations.